Perancangan User Experience Aplikasi Media Pembelajaran Interaktif Berbasis Mobile Pada Materi Geometri Dimensi Tiga Dengan Metode Human Centered Design - Iqbal Setya Nurfimansyah; Komang Candra Brata; Ahmad Afif Supianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Geometry has sub-sections, namely three dimensions which talk about spatial shapes. Building space contains three important elements, namely length, width, and height so that it is said to be a three-dimensional shape. Three dimensional learning, must start with real objects with three dimensions, then it can be implemented through images that seem to look like two dimensional shapes. To realize three-dimensional images at this time, it can be done with the help of technology, namely mobile applications to make it easier in the abstraction process. This study aims to simplify the process of building abstraction involving user experience as a reference in designing solution designs made for high school, vocational, and MA students to assist in the learning process. The Human Centered Design method is used to place potential users in the main center of research by providing a good user experience. There are four main stages that are carried out in the development of research. The first analysis is in the form of user analysis then persona to emphaty map. The two identifications are in the form of features and user tasks. The three implementations are wireframe design, screenflow and prototype. The fourth evaluation is in the form of usability test and system usability scale test. Derived from the testing process carried out resulted in an efficiency of 0.181 and 100% effectiveness as well as 64.17 for user satisfaction which means that it is considered sufficient. Therefore, it can be concluded that the design of the solution that has been given is quite successful in solving the problem even though it has satisfaction, there are several shortcomings.